Microstructures and mechanical properties of leaded aluminium alloys - Tiwari S.N.; Pathak J.P.; Malhotra S.L. (My University, 2025)
An impeller-mixing, bottom-discharge chill-casting technique has been used to produce a series of new bearing alloys varying in lead content from 5 to 50 wt-% and differing in base metal over a range comprising commercially pure aluminium and a number of much stronger aluminium-base alloys. The as-cast microstructures of lead-bearing alloys have been studied using optical and scanning electron microscopy. The room-temperature UTS, compressive and tensile proof stresses, hardness, elongation, and impact strength of these alloys have heen investigated as a function of composition. The influence of heat and thermomechanical treatments on the as-cast mechanical properties has also been evaluated. The results reveal that several combinations of strength, hardness, ductility, and toughness can be generated from the alloys to meet the needs of a variety of bearing and other antifriction applications. A comparison of the mechanical properties of leaded alloys with those of existing bearing alloys shows that the new alloys might be preferable for similar applications. © 1983, The Metals Society. All rights reserved.